Cloning, expression analysis and functional characterization of an interleukin-1 receptor-associated kinase 4 from Apostichopus japonicus. (September 2018) - Cui, Yi; Jiang, Liting; Xing, Ronglian; Wang, Zhengdong; Wang, Zhenhui; Shao, Yina; Zhang, Weiwei; Zhao, Xuelin; Li, Chenghua
Highlights: Full-length cDNA of Interleukin 1 receptor-associated kinase 4 were identified in Apostichopus japonicus . AjIRAK4 was ubiquitously expressed in all examined tissues with the larger magnitude in muscle. AjIRAK4 mRNA in coelomocytes was up-regulated after Vibrio splendidus challenge or LPS exposure. Silencing AjIRAK4 could inhibit the expression of TLR members at mRNA and protein levels in vitro and in vivo . Knockdown of AjIRAK4 resulted in the significant promotion of coelomocyte apoptosis and induced AjBax expression. Abstract: Interleukin 1 receptor-associated kinase 4 (IRAK4) is a key factor in TLR-mediated host immune function. In this study, an IRAK4 homologue molecule was identified from Apostichopus japonicus (designated as AjIRAK4) by RACE approach. The full-length cDNA of AjIRAK4 was of 2024 bp containing an open reading frame of 1311 bp encoding a 436-amino-acid (aa) residue polyprotein with the typical death domain (10-113aa) and the kinase domain (160-426aa). The mRNA transcripts of AjIRAK4 displayed constitutively expressed in all examined tissues with highest expression in the muscles (7.20-fold increase compared to the coelomocytes). The pathogen Vibrio splendidus challenge and LPS exposure could both significantly up-regulate the mRNA expression of AjIRAK4. Silencing AjIRAK4 in vitro and in vivo could inhibit the expression of TLR members at mRNA and protein levels, suggesting AjIRAK4 was an important component of TLR cascade in sea cucumber. More importantly, knockdown of AjIRAK4 by specific siRNA resulted in the significant promotion of coelomocyte apoptosis by 1.82-fold increase in vitro and 1.95-fold in vivo . Taken together, all our results suggested that AjIRAK4 might be served as coelomocyte apoptosis regulator via TLR cascade.